A Mini Review: Hybridized Electric Discharge Machining. Issue 1 (April 2021) - Agrawal, Manoj Kumar; Sonia, Pankaj
Abstract: The miniaturization of technology in global current scenario make a necessity to innovate a new technology to meet the requirement. The machining and finishing is animportant operation of any manufacturing process and the miniaturization of technology create a need to invent a machining processes for micro and nanoscale machining for high strength alloys, sensitive material and environment. The hybridization of various conventional and un-conventional machining is the way to satisfy the adversative machining conditions by combining the two or many machining processes. The presented work reviewed the assistance of electric discharge machining (EDM) by various other processes or energy and impact of Laser assistance tomany other process by discussing their positive and deleterious aspects.